Mesopelagic Mesozooplankton and Micronekton Database - Yulia Egorova; Evgeny A. Pakhomov; Ian McIvor; Andrea Le; Tymofiy Spesivy (Scientific Data)
Abstract The Mesopelagic Mesozooplankton and Micronekton Database (MMMD) compiles quantitative data on the distribution and density of mesopelagic (200–1000 m) mesozooplankton and micronekton (0.2–20 mm and 20–200 mm) species, using 258 published and unpublished sources spanning from 1880 to 2016. This extensive dataset includes 266,611entries, covering a broad temporal, spatial range and diel changes with varying levels of completeness. The data were standardized to address inconsistencies in sampling methods, mesh sizes, and taxonomic classifications. Despite some limitations, including gaps in spatial and depth coverage, the database provides a valuable resource for the mesopelagic macro-ecological research, which is updatable. Comparisons with existing databases underscore its unique contributions to the study of mesopelagic ecosystems.